Iraq : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2021)
Iraq's socio-economic fragilities have been severely aggravated by the pandemic and the sharp decline in oil revenues, which arrived on the heels of widespread social unrest and political instability. The health system's limited capacity has been strained, while the fiscal position has become untenable as oil revenues declined sharply to a level that barely covers the government's large wage and pension bills. Although the number of new infections declined recently, Iraq registered the second-highest COVID-related fatalities in the region, and the fiscal response to the pandemic has been one of the lowest. A six-month political paralysis preceding the formation of the government in May 2020 and plans to hold early parliamentary elections in mid-2021 have been weighing on political support for reforms. Risks of social unrest, geopolitical tensions, and insecurity remain elevated.